Pengaruh Kejelasan Sasaran Anggaran Terhadap Kesenjangan Anggaran Dengan Asimetri Informasi Sebagai Variabel Pemoderasi - Richard Arya Prakasa (Universitas Negeri Padang, 2020)
This study aimed to determine the effect of budget goal clarity to the budgetary slack to be moderated by the information asymmetry. This research was conducted in SKPD Pesisir Selatan District as much as 27 SKPD. The respondents used in this study were 108 employees. Sample selection was done by using purposive sampling method. Data collection was done through questionnaire.The analysis technique used in this research his Moderated Regression Analysis.The results of this study found that, budget goal clarity does not affect the budgetary slack and the information asymmetry cannot moderate the influence of budget goal clarity for budgetary slack.